Efficacy of Individual Bacteriophages Does Not Predict Efficacy of Bacteriophage Cocktails for Control of Escherichia coli O157 - Niu, Yan D.; Liu, Hui; Du, Hechao; Meng, Ruiqiang; Sayed Mahmoud, El; Wang, Guihua; McAllister, Tim A.; Stanford, Kim (Frontiers in Microbiology, 2021)
Effectiveness of bacteriophages AKFV33 (Tequintavirus, T5) and AHP24 (Rogunavirus, T1); wV7 (Tequatrovirus, T4) and AHP24S (Vequintavirus, rV5), as well as eleven cocktails of combinations of the four phages were evaluated in vitro for biocontrol of six common phage types of Escherichia coli O157 (human and bovine origin) at different multiplicities of infection (MOIs; 0.01 to 1000), temperatures (37°C or 22°C) and exposure times (10 to 22 h). Phage efficacy against O157 was highest at MOI 1000 (P < 0.001) and after 14−18 h of exposure at 22°C (P < 0.001). Activity of individual phages against O157 did not predict activity of a cocktail of these phages even at the same temperature and MOI. Combinations of phages were neutral (no better or worse than the most effective constituent phage acting alone), displayed facilitation (greater efficacy than the most effective constituent phage acting alone) or antagonistic (lower efficacy than the most effective constituent phage acting alone). Across MOIs, temperatures, exposure time and O157 strain, a cocktail of T1, T4 and rV5 was most effective (P < 0.05) against O157 even though T1 and rV5 were less effective (P < 0.001) than other individual phages. T5 was the most effective individual phage (P < 0.05), but was antagonistic to other phages, particularly rV5 and T4 + rV5. Interactions among phages were influenced by phage genera and phage combination, O157 strain, MOIs, incubation temperature and time. Based on this study, future development of phage cocktails should, as a minimum, include confirmation of a lack of antagonism among constituent phages, and preferably confirmation of facilitation or synergistic effects.